Proton Catalysis in the Redox Responsivity of a Mini‐Sized Photochromic Diarylethene. Issue 37 (23rd July 2013) - Massaad, Julie; Micheau, Jean‐Claude; Coudret, Christophe; Serpentini, Charles Louis; Guirado, Gonzalo
Abstract A thermally irreversible dithienylethene (DTE) photochrom can be turned into a thermally reversible one in presence of CuII triflate. A ring opening (DTEC closed→DTEO open) occurs through the formation of a copper‐containing fast transient intermediate. Stopped‐flow experiments monitored at 410 and 780 nm have allowed to show that the stoichiometry of this intermediate is DTE/Cu=1:1. At longer monitoring times (i.e., several seconds after mixing), the intermediate undergoes a slow decay while the residual DTEC closed form opens. A joint detailed kinetic and electrochemical analysis has unveiled a proton catalysis scenario in which electron transfer between DTEC and CuII, ligand exchange, protonation‐deprotonation equilibria of the cation radicals and ring opening are embedded into two main reaction cycles. At the beginning of the reaction, CuII is reduced into CuI and DTE is degraded without ring opening. Then, as the reaction progresses, the triflic acid released from the CuII reduction switches‐on a propagation cycle during which ring opens without any more CuII consumption. Cyclic voltammetry, spectro‐electrochemical measurements, delayed photocoloration experiments in presence of CuII and acid–base additions have confirmed the main features of the proton catalysis.